(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: The study aims to describe the current status of surgical hand hygiene compliance of medical staff at Tam Anh General Hospital, Hanoi, period 2024-2025. Research design: Cross-sectional research design, conducted from June 1, 2025 to September 30, 2025 based on the electronic monitoring board of hand hygiene procedures of each hand hygiene at 223 surgeries at Tam Anh General Hospital, Hanoi from July 2024 to June 2025. Results: The rate of compliance with hygiene and infection control of medical staff is 77.9%, of which the instrument nurse has the highest compliance rate of 91.1%, the lowest is the anesthetist/technician with 68%. The IVF department has the lowest rate of compliance with hygiene and infection control. From the third quarter of 2024 to the second quarter of 2025, the rate of compliance with hygiene and infection control gradually increased. The means for hygiene and infection control are not adequate. Conclusion: Compliance with hygiene and infection control of medical staff has had positive changes, but has not yet met the requirements. The hospital’s board of directors needs to have a plan to supplement the missing means and implement appropriate solutions to enhance compliance with hygiene and infection control of medical staff.